2010
DOI: 10.1103/physrevb.81.224420
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the magnetic phase diagram of the frustrated metamagnetCuFeO2

Abstract: The magnetic phase diagram of CuFeO2 as a function of applied magnetic field and temperature is thoroughly explored and expanded, both for magnetic fields applied parallel and perpendicular to the material's c-axis. Pulsed field magnetization measurements extend the typical magnetic staircase of CuFeO2 at various temperatures, demonstrating the persistence of the recently discovered high field metamagnetic transition up to TN2 ≈ 11 K in both field configurations. An extension of the previously introduced pheno… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
34
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 45 publications
(182 reference statements)
3
34
0
1
Order By: Relevance
“…In particular, magnetoelastic coupling can reduce the slope of the acoustic phonon dispersion branches [56] in the energy region well below 3 meV, which, in turn, would result in an increased "Debye level" at low phonon energies. Thus, the considerable underestimation of the average phonon group velocity by means of NIS may point towards a significant spinphonon coupling, which was already shown to be necessary in order to model the magnetic behavior [3,21] of CuFeO 2 . In addition to ultrasound-based investigations [22,23], the present results concerning the low-energy region indicate that magnetoelastic coupling persists in the paramagnetic phase of CuFeO 2 as well.…”
Section: Nisul S Was Calculated By Identifying L D With G(e)/ementioning
confidence: 99%
See 3 more Smart Citations
“…In particular, magnetoelastic coupling can reduce the slope of the acoustic phonon dispersion branches [56] in the energy region well below 3 meV, which, in turn, would result in an increased "Debye level" at low phonon energies. Thus, the considerable underestimation of the average phonon group velocity by means of NIS may point towards a significant spinphonon coupling, which was already shown to be necessary in order to model the magnetic behavior [3,21] of CuFeO 2 . In addition to ultrasound-based investigations [22,23], the present results concerning the low-energy region indicate that magnetoelastic coupling persists in the paramagnetic phase of CuFeO 2 as well.…”
Section: Nisul S Was Calculated By Identifying L D With G(e)/ementioning
confidence: 99%
“…Besides, the layered structure of CuFeO 2 suggests a pronounced vibrational anisotropy, which is yet to be confirmed. Furthermore, in contrast to the magnetic ground state at zero magnetic field and magnetic phases at high fields, which generally exhibit rather well defined spin structures [3,4], the magnetic ITP has received considerably less attention and is not yet convincingly described.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, if the lattice distortion were suppressed by pressure, the magnetic LRO could not be stabilized and novel magnetic states such as spin liquids [5] and spin nematics [6,7] would be expected. In the present study, we examined the effect of pressure on magnetic ordering in the frustrated spin-lattice coupling system of CuFeO 2 .Since the discovery of the spontaneous spin-lattice coupling phenomenon in the frustrated triangular lattice antiferromagnet CuFeO 2 , [8,9] spin-lattice coupling has been extensively studied using high-field X-ray diffraction, [10, 11] ultrasonic velocity,[12] magnetization measurements, [13] and Landau theory approaches. [14] These studies have demonstrated that spontaneous spinlattice coupling plays an essential role in the stabilization of the magnetic ground state of CuFeO 2 .…”
mentioning
confidence: 99%